(untitled) (Medico Legal Update, 2024)
Background: Road traffic injuries are the major health problems and leading cause of death and injury around the world. This study was conducted in order to observe the pattern of external injuries and internal injuries. In many set ups there may not be adequate facilities for investigations like imaging. If it is possible to know the common patterns in external and internal injuries it would be possible to give appropriate care and prioritise the treatment. Methods: An autopsy based prospective study was conducted during the period 2011 to 2013 in the Department of Forensic Medicine after obtaining ethical clearance The pattern of external and visceral injuries in cases of motorised two wheeler accidents were observed and documented. Conclusion: Out of 37 cases examined at autopsy Among external injuries Abrasions are commonly seen involving the whole body. Among Visceral injuries Contusions are seen more in Lungs followed by Kidney Spleen, Heart and Liver.Among laceration Liver has the most followed by lung and Spleen.